2020
DOI: 10.1007/s13205-020-02512-x
|View full text |Cite
|
Sign up to set email alerts
|

The saltern-derived Paludifilum halophilum DSM 102817T is a new high-yield ectoines producer in minimal medium and under salt stress conditions

Abstract: In the present study, the growth conditions and accumulation of ectoines (ectoine and hydroxyectoine) by Paludifilum halophilum DSM 102817 T under salt stress conditions have been investigated. The productivity assay of this strain for ectoines revealed that the highest cellular content was reached in the minimal glucose sea water medium (SW-15) within 15% salinity. The addition of 0.1% (w/v) aspartic acid to the medium allowed an average of four times higher biomass production, and a dry mycelial biomass of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Such a challenging habitat requires active measures by this halophile to counteract the out ow of water from the cells and to optimize the solvent properties of the cytoplasm for biochemical reactions and the functionality of cell components (Czech et al 2018a). Analysis of the physiological response of P. halophilum revealed that this bacterium uses the salt-out strategy through the accumulation of ectoines at relatively high yields (Ayadi et al 2020). The data presented here support this conclusion and highlight the ability of P. halophilum to cope with a broad spectrum of salinities ranging from 5 to 20 %.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a challenging habitat requires active measures by this halophile to counteract the out ow of water from the cells and to optimize the solvent properties of the cytoplasm for biochemical reactions and the functionality of cell components (Czech et al 2018a). Analysis of the physiological response of P. halophilum revealed that this bacterium uses the salt-out strategy through the accumulation of ectoines at relatively high yields (Ayadi et al 2020). The data presented here support this conclusion and highlight the ability of P. halophilum to cope with a broad spectrum of salinities ranging from 5 to 20 %.…”
Section: Discussionmentioning
confidence: 99%
“…Strain culture conditions P. halophilum DSM 102817 T was routinely cultivated in an optimized mineral sea water (SW) medium (Ayadi et al 2020) aspartic acid. The pH of the growth medium was adjusted to 8.3-8.4 with 4 M NaOH, and the osmolarity the the set-up of the individual experiments by adding NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation